Common Problems in Acute Care Surgery - Moore, Laura J.; Turner, Krista L.; Todd, S. Rob (Springer New York : Imprint: Springer, 2013)
The current medical literature contains ample text addressing the topics of trauma and critical care. However, there are few texts existing that specifically address the common surgical problems encountered by practicing acute care surgeons. Common Problems in Acute Care Surgery provides a comprehensive, evidence-based review of the most common clinical problems encountered by acute care surgeons. Focusing on the clinical care of the patient, this volume explores the general principles of acute care surgery and the specific disease states that are commonly encountered by acute care surgeons. The work also touches upon the ethical issues and systems development behind acute care surgery,  including practical considerations for establishing an acute care surgery program, ethical considerations in acute care surgery, and the role of palliative care. Authored by respected experts in the field and illustrated throughout with detailed photographs, Common Problems in Acute Care Surgery is of great value to resident surgeons in training, fellows, and practicing surgeons in acute care surgery.